PROSES COLLABORATIVE GOVERNANCE DALAM KEBIJAKAN KABUPATEN LAYAK ANAK (KLA) PADA KLASTER V PERLINDUNGAN KHUSUS DI KABUPATEN PEMALANG - Adelia Nuriawati, Sekar; Hanani, Retna; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
The implementation of the KLA policy in Cluster V special protection in Pemalang Regency lacks optimization, necessitating collaborative efforts for maximal effectiveness. This study aims to analyze Collaborative Governance processes and identify success factors in KLA policy implementation. The research employs qualitative methods, utilizing Ansell and Gash's Collaborative Governance theory and DeSeve's theory to indentify the successes factor. Data collection includes observations, interviews, and document analysis. Findings reveal face-toface dialogues by Tim Gugus Tugas KLA, fostering trust, positive policy image construction, and stakeholder engagement. Commitment to children's rights persists despite varying actor roles. While mutual understanding dissemination remains incomplete, it's addressed through socialization endeavors. Preliminary results indicate Pemalang Regency's in a Nindya predicates. The driving factors of Collaborative Governance include collaborative, transparent and participatory discussions, well-defined procedures, clear distribution of responsibility, stakeholder interdependence, and diverse communication channels. Inhibiting factors include resource limitations (human and budget’s resources), stakeholder inconsistency, complexity of stakeholder’s role and indicators, also the evolutionary of policy information. Recommendations include enhancing implementer quality trough involving child psychology experts, optimizing information dissemination, and expanding collaboration networks with private sector can be maximized